Culture of Microalgae with Ultrafiltered Seawater: A Feasibility Study - Clémence Cordier; Killian Guyomard; Christophe Stavrakakis; Patrick Sauvade; Franz Coelho; Philippe Moulin (Ital Publication, 2020)
The culture of microalgae is important for the production and maintenance of bivalves. One of the major challenges is to maintain the reliability of microalgae forages over the long term. The aim of this work is to use Ultrafiltered (UF) seawater to cultivate them. Thus, cultures in a volume of 300 L of 2 species of microalgae Tetraselmis and T-isochrysis, were monitored in UF water (membrane pore size: 20 nm) and in sea water usually used on the Ifremer mollusk experimental platform of Bouin (France) (Prefiltration, 3 filtrations and 2 UV). The major result is the securing of microlagae cultures with the absence of parasites in all cultures supplied with ultrafiltered water, unlike analyses of the various control cultures. In the case of T-isochrysis, 3 cultures out of 4 resulted in higher microalgae concentrations, up to 30%, in ultrafiltered water thus bringing a benefit on the algal density. These conclusions and the ease of recovering water (linked to the reduction in treatment stages) allowed a transfer of technology. In fact the 300 L cultures hitherto carried out on the experimental platform are now produced in ultrafiltered water since early 2019.